Effectiveness of Using Snakes and Ladders Media In Algebra Mathematics Learning to Improve Students' Motivation and Learning Outcomes in Class VII of Junior High School - Layn, Muhamad Ruslan; Abd. Rahman; Rosidah (International journal of technology and education research, 2026)
This study aims to determine the effectiveness of using snakes and ladders media in algebraic mathematics learning to improve motivation and learning outcomes of class VII students at SMP Negeri 6 Sorong City. The problem raised in this study is the low learning motivation and learning outcomes of students in algebra material due to less interactive learning methods. This study uses a mix method approach with a one group pre-test and post-test design. The research subjects were 29 class VII students. The instruments used included observation of learning implementation, student activity observation sheets, tests (pre-test and post-test), and motivation questionnaires. The results of the study showed that learning with snakes and ladders media with a research instrument percentage of 91% was in the